Parvalbumin Interneuron Disorders Triggered by Oxidative Stress as a Common Mechanism Causing Schizophrenia in the Elderly: a Literature Review Study - Siswanto; Mindiroeseno, Arief Mukti (Formosa Journal of Social Sciences (FJSS), 2023)
Schizophrenia is a functional psychotic disorder with the main disturbance of the thought process and the disintegration of the thought process, affect or emotion, volition and psychomotor accompanied by a distortion of reality, especially due to delusions and hallucinations, fragmented associations resulting in incoherence, inadequate affect and emotion, and psychomotor which shows withdrawal, ambivalence and bizzare behavior. The research design used is the literature review method. Literature study is research carried out by researchers by collecting a number of articles or journals related to research problems and objectives. The study results show that various literature shows evidence that schizophrenia in the elderly occurs due to changes in antioxidant enzymes in schizophrenia. Increased levels of lipid peroxidation products and nitric oxide (NO) occurred in schizophrenia, while superoxide dismutase activity was found to decrease significantly in this disorder, but glutathione peroxidase and catalase activity had no effect in schizophrenia patients. In schizophrenic patients, it was found that there was an increase in the production of free radicals, therefore the administration of anti-oxidants is necessary to increase antioxidants which can reduce symptoms in schizophrenic patients.